Effect of sprouting and weather damage on feeding value of grain sorghum (summary of beef, swine, and poultry trials) - H. Turlington; G. Allee; Jack G. Riley; Ronald V. Pope (Kansas Agricultural Experiment Station Research Reports, 1987)
Grain sorghum officially graded as 39% damaged (sprouted) with 10% broken kernels or foreign material was fed to beef steers, growing swine, and broilers to compare its feeding value to that of normal grain sorghum. Damaged grain constituted 0, 50, or 100% of the grain portion of the rations. Cattle performance during a 57-day finishing period was not reduced by feeding sprouted grain sorghum. However, the swine and broiler trials suggest that sprouted grain sorghum has a slightly lower energy value.
Keywords: Cattlemen& #x27; s Day; 1987; Kansas Agricultural Experiment Station contribution; no. 87-309-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 514; Beef; Sprouting; Weather damage; Grain sorghum